Proteomic characterization of pleural effusion, a specific host niche of Mycoplasma mycoides subsp. mycoides from cattle with contagious bovine pleuropneumonia (CBPP) - Weldearegay, Yenehiwot Berhanu; Pich, Andreas; Schieck, Elise G.; Liljander, Anne M.; Gicheru, N.; Wesonga, H.O.; Thiaucourt, Francois; Kiirika, L.M.; Valentin-Weigand, Peter; Jores, Joerg; Meens, J. (Elsevier, 2016)
Mycoplasma mycoides subsp. mycoides (Mmm) is the causative agent of contagious bovine pleuropneumonia (CBPP), a severe pleuropneumonia in cattle. The abnormal accumulation of pleural fluid, called pleural effusion (PE), is one of the characteristics of this disease. We performed a proteomic analysis of seven PE samples from experimentally infected cattle and characterized their composition with respect to bovine and Mmm proteins. We detected a total of 963 different bovine proteins. Further analysis indicated a strong enrichment of proteins involved in antigen processing, platelet activation and degranulation and apoptosis and an increased abundance of acute phase proteins. With regard to the pathogen, up to 108 viable mycoplasma cells per ml were detected in the PE supernatant. The proteomic analysis revealed 350 mycoplasma proteins, including proteins involved in virulence-associated processes like hydrogen peroxide (H2O2) production and capsule synthesis. The bovine proteins detected will aid to characterize the inflammasome during an acute pleuropneumonia in cattle and the identified mycoplasma proteins will serve as baseline data to be compared with in vitro studies to improve our understanding of pathogenicity mechanisms. Based on our results, we named the pleural effusion an “in vivo niche” of Mmm during the acute phase of CBPP. Biological significance This is the first study on bovine pleural effusions derived from an infectious disease and the first approach to characterize the proteome of Mycoplasma mycoides in vivo. This study revealed a high number of viable Mmm cells in the pleural effusion. The bovine pleural effusion proteome during Mmm infection is qualitatively similar to plasma, but differs with respect to high abundance of acute phase proteins. On the other hand, Mmm in its natural host produces proteins involved in capsule synthesis, H2O2 production and induction of inflammatory response, supporting previous knowledge on mechanisms underlying the survival and virulence of this pathogen while inside the natural host. This knowledge forms a profound basis for testing the identified protein candidates for diagnostics or vaccines.